﻿A new species of spiny-backed tree frog, genus Osteocephalus (Anura, Hylidae), from the Yanachaga Chemillén National Park in central Peru - Pablo J. Venegas; Luis A. García-Ayachi; Eduardo Toral; José Malqui; Santiago R. Ron (Evolutionary Systematics, 2023)
We describe a new species of Osteocephalus Fitzinger, 1843 using morphological traits of adult frogs and its larvae, as well as molecular evidence. The new species occurs in the premontane forest of the Cordillera del Yanachaga in the Andes of central Peru, at elevations between 1000 and 1150 m a.s.l. It belongs to the Osteocephalus mimeticus species group and is the sister species of O. mimeticus. It is most similar to three species with predominantly dark irises, tuberculate dorsal skin, and brown dorsal coloration: O. festae Peracca, 1904, O. mimeticus Melin, 1941, and O. verruciger Werner, 1901. Of these three species, the most similar is O. mimeticus. However, the new species can be easily distinguished from O. mimeticus by having a cream or creamy-tan venter with a well-defined pattern of brown chocolate blotches and flecks (venter cream, tan, or brown without marks in O. mimeticus). The tadpoles of O. vasquezi sp. nov. are strikingly different from the tadpoles of O. mimeticus by having a larger oral disk with nine lower labial tooth rows (only six in O. mimeticus). Tadpoles of the new species and those of O. festae are unique among Osteocephalus by belonging to the suctorial ecomorphological guild as shown by their large oral disks. Our time tree suggest that the new species diverged from its sister species at the beginning of the Pleistocene, ~2.5 million years ago.